Nucleic acid-based vaccines targeting respiratory syncytial virus: Delivering the goods - Trevor R. F. Smith; Katherine Schultheis; Kate E. Broderick (Human Vaccines & Immunotherapeutics, 2017)
Respiratory syncytial virus (RSV) is a massive medical burden on a global scale. Infants, children and the elderly represent the vulnerable populations. Currently there is no approved vaccine to protect against the disease. Vaccine development has been hindered by several factors including vaccine enhanced disease (VED) associated with formalin-inactivated RSV vaccines, inability of target populations to raise protective immune responses after vaccination or natural viral infection, and a lack of consensus concerning the most appropriate virus-associated target antigen. However, with recent advances in the molecular understanding of the virus, and design of highly characterized vaccines with enhanced immunogenicity there is new belief a RSV vaccine is possible. One promising approach is nucleic acid-based vaccinology. Both DNA and mRNA RSV vaccines are showing promising results in clinically relevant animal models, supporting their transition into humans. Here we will discuss this strategy to target RSV, and the ongoing studies to advance the nucleic acid vaccine platform as a viable option to protect vulnerable populations from this important disease.